Folate Intake and Markers of Folate Status in Women of Reproductive Age, Pregnant and Lactating Women: A Meta-Analysis. (13th September 2012) - Berti, Cristiana; Fekete, Katalin; Dullemeijer, Carla; Trovato, Monica; Souverein, Olga W.; Cavelaars, Adriënne; Dhonukshe-Rutten, Rosalie; Massari, Maddalena; Decsi, Tamás; van't Veer, Pieter; Cetin, Irene
Abstract : Background . Pregnant and breastfeeding women are at risk for folate deficiency. Folate supplementation has been shown to be associated with enhanced markers of folate status. However, dose-response analyses for adult women are still lacking. Objective . To assess the dose-response relationship between total folate intake (folic acid plus dietary folate) and markers of folate status (plasma/serum folate, red blood cell folate, and plasma homocysteine); to evaluate potential differences between women in childbearing age, pregnant and lactating women. Methods . Electronic literature searches were carried out on three databases until February 2010. The overall pooled regression coefficient ( β ) and SE( β ) were calculated using meta-analysis on a double-log scale. Results . The majority of data was based on nonpregnant, nonlactating women in childbearingage. The pooled estimate of the relationship between folate intake and serum/plasma folate was 0.56 (95% CI = 0.40–0.72, P < 0.00001 ); that is, the doubling of folate intake increases the folate level in serum/plasma by 47%. For red blood cell folate, the pooled-effect estimate was 0.30 (95% CI = 0.22–0.38, P < 0.00001 ), that is, +23% for doubling intake. For plasma-homocysteine it was –0.10 (95% = –0.17 to –0.04, P = 0.001 ), that is, –7% for doubling the intake. Associations tended to be weaker in pregnant and lactating women. Conclusion . Significant relationships between folate intake and serum/plasma folate, red blood cell folate, and plasma homocysteine were quantified. This dose-response methodology may be applied for setting requirements for women in childbearing age, as well as for pregnant and lactating women.